2022
DOI: 10.1186/s13104-022-06073-5
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoglucomutase 1 contributes to optimal cyst development in Toxoplasma gondii

Abstract: Objective Toxoplasma gondii is a ubiquitous parasite of medical and veterinary importance; however, there exists no cure for chronic toxoplasmosis. Metabolic enzymes required for the production and maintenance of tissue cysts represent promising targets for novel therapies. Here, we use reverse genetics to investigate the role of Toxoplasma phosphoglucomutase 1, PGM1, in Toxoplasma growth and cystogenesis. Results We found that disruption of pgm1 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…Recent work has also demonstrated that loss of phosphoglucomutase 1, an enzyme related to AG metabolism, results in smaller cysts (70). Our prior work established that bradyzoite replication within tissue cysts occurs in a cyclical pattern that is reflected in the packing density of bradyzoites within the cyst (7).…”
Section: Resultsmentioning
confidence: 99%
“…Recent work has also demonstrated that loss of phosphoglucomutase 1, an enzyme related to AG metabolism, results in smaller cysts (70). Our prior work established that bradyzoite replication within tissue cysts occurs in a cyclical pattern that is reflected in the packing density of bradyzoites within the cyst (7).…”
Section: Resultsmentioning
confidence: 99%